Exploiting APC Function as a Novel Cancer Therapy - C. Lesko, Alyssa; H. Goss, Kathleen; R. Prosperi, Jenifer (Current Drug Targets, 2014)
The Adenomatous Polyposis Coli (APC) tumor suppressor is most commonly mutated in colorectal cancers such as familial adenomatous polyposis (FAP); as well as many other epithelial cancers like breast, pancreatic, and lung cancer. APC mutations usually result in a truncated form of the protein lacking the carboxy-terminal region resulting in loss of function. Mutations in APC have been identified in early stages of cancer development making it a gatekeeper of tumor progression and therefore an ideal therapeutic target. APC is best known for its role as a negative regulator of the Wnt/β -catenin pathway. However, APC also mediates several other normal cell functions independently of Wnt/β-catenin signaling such as apical-basal polarity, microtubule networks, cell cycle, DNA replication and repair, apoptosis, and cell migration. Given the vast cellular processes involving APC, the loss of these
Keywords: APC